Application of delayed luminescence measurements for the identification of herbal materials: a step toward rapid quality control - Mengmeng Sun; Shengpeng Wang; Yong Jing; Li Li; Min He; Yusheng Jia; Eduard van Wijk; Yitao Wang; Zhihong Wang; Mei Wang (BMC, 2019)
Abstract Background Herbal materials are widely used as medicinal products, dietary supplements, food, and spices. With increased consumption, the safety, quality, and efficacy of herbal materials are becoming more relevant. The authenticity of herbal materials plays an important role in herbal quality control, and there is an urgent need to develop a simple, direct, objective, rapid, and inexpensive measurement tool for the identification of herbal materials for the purpose of quality control. Methods Delayed luminescence (DL) was used to measure authentic and counterfeit herbal materials. A hyperbolic function was used to extract four properties from the DL curves of the herbal materials. Statistical tools, including Student's t test and Principal Component Analysis, were used to differentiate authentic and counterfeit herbal materials based on the DL properties. Results Our results showed that authentic and counterfeit herbal materials could be identified based on the DL properties as follows: (a) authentic versus counterfeit materials; (b) authentic versus adulterated materials; (c) authentic versus sulfur-fumigated materials; as well as (d) authentic versus dyed materials. Conclusion The simple, direct, rapid, and inexpensive measurements offered by DL potentially offer a novel technique for the identification of Chinese herbal materials. However, the establishment of a valid database will be the next step toward the possible application of this technique, which would contribute significantly to the development of a novel digital tool for the quality control of herbal materials.